Performance evaluation of reinforced earth walls with sustainable backfills subjected to railway loading - Mandloi, Pushpraj; Hegde, Amarnath (Frontiers in Built Environment, 2022)
The concept of using Reinforced Earth (RE) walls for rail corridors is gaining popularity. As of now, very few nations have successfully adopted the RE walls for Railway infrastructure. These structures require good quality granular materials like sand for backfilling. However, due to the scarcity of good quality natural sand, research efforts are being made to look for cost effective alternatives to sand in backfill applications. The present study examines the possibilities of using the two sustainable materials, namely steel slag and construction and demolition waste (CDW), as backfills in RE walls subjected to harmonic train-induced load. In total, 63 separate full-scale numerical models of RE walls have been analyzed to understand the wall behavior with sustainable backfills subjected to different train speeds. The backfill materials were simulated with three different material models, namely, linear elastic, Mohr-Coulomb and Hardening Soil, for comparison. The results showed that the RE wall behavior is highly frequency-dependent. RE walls with steel slag and CDW backfills have shown 25% and 12% lesser deformations, respectively as compared to the sand backfill. Furthermore, reinforcement tensile forces in walls with sustainable backfills were found to be comparable to those of sand. The maximum deformation of the wall was observed when the fill materials were simulated with the Hardening Soil model. In overall, satisfactory performance of the RE wall was observed in the presence of sustainable backfill materials under Railway loading.